Strong Under‐Ice Heating of Central Asian Shallow Lakes - Puzhen Huo; Peng Lu; Matti Leppäranta; Georgiy Kirillin; Bin Cheng; Fei Xie; Zhijun Li (Geophysical Research Letters, 2025)
Abstract Shallow lakes (<2 m depth) of Central Asian, receiving strong solar radiation and low precipitation, are sensitive to atmospheric forcing because of their low heat capacity, yet their under‐ice thermal conditions remain poorly investigated. We conducted the first complete ice season monitoring of Lake Ulansu (Ulansuhai, Wuliangsuhai), revealing unique thermal behavior. The lake was salinity stratified (<3‰), stabilizing the lower water layer and allowing the water temperature to reach 10°C before break‐up. The solar radiation absorbed by the water (Qsw) drove the water–ice heat flux, with approximately 82% of Qsw returning to the ice base, facilitating a rapid shift from convective mixing to stable stratification. These findings provide key insights into the thermal regimes of Central Asian shallow lakes, informing climate models and ecological assessments for more than 10,000 similar lakes in the region.